Prevalence, correlative and statistical relationships of renal dysfunction in patients with chronic ischemic heart failure - D. A. Lashkul (Zaporožskij Medicinskij Žurnal)
Chronic heart failure (CHF) is one of the most common complications of cardiovascular disease. According multicenter studies conducted during recent years, coronary heart disease was the leading cause of heart failure and has been on average 64% of patients with chronic heart failure. The tight functional relationship of cardiovascular and urinary system causes a lot of interest to the functional state of kidneys in various cardiovascular diseases. Most risk factors for cardiovascular disease are common risk factors of renal failure. Causes significant differences in the prevalence of chronic kidney disease (CKD) in patients with chronic heart failure, defined as coronary artery disease and hypertension remain unclear. Need clarification prevalence of CKD among patients with CHF in general and in specific groups of patients.